If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3 + -1x = 6 Reorder the terms: 3 + 2x + -1x = 6 Combine like terms: 2x + -1x = 1x 3 + 1x = 6 Solving 3 + 1x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 1x = 6 + -3 Combine like terms: 3 + -3 = 0 0 + 1x = 6 + -3 1x = 6 + -3 Combine like terms: 6 + -3 = 3 1x = 3 Divide each side by '1'. x = 3 Simplifying x = 3
| 7y^2-4y-6= | | 6x+-1=x+13 | | s+2.5=6.25 | | 6(2X-4)=-32 | | -38=5x-x+10 | | 3x+(x+2)=20 | | 10x+-1=8x+6 | | 3x+9-x+4-2x=18 | | 9-24u+16u^2= | | 5x+-1=2x+11 | | 81-18s-3s^2= | | 7(x+3)-2(3x+1)=25 | | y^2+64=0 | | 38-30v=32 | | 150-5s-5s^2= | | 12x+-4=8x+24 | | 4x+0y+2z=24.94 | | 11-6x^2-31x= | | 6x+4y+1z=36.39 | | -7+7x-x=-1 | | 13-12d^2-35d= | | 10x+-6=7x+9 | | x=4.2375+-0.5y | | x^2+9x+20.25=-2+20.25 | | 9y+-11=-2 | | 4x+2y=16.95 | | 10+-21=7x | | 1507+20x=1767 | | 6c^3+8c^2-30c= | | 7x-27x=0 | | 1507+20=1767 | | 14=-7x+5x+8 |